2009
DOI: 10.1007/s12231-009-9102-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Local Value of Non-Timber Forest Products to Pendjari Biosphere Reserve Dwellers in Benin

Abstract: This paper uses an indices method based on participant ranking of species to quantify use-values of Non-Timber Forest Products (NTFPs) and the socio-economic factors that influence these values for people living around the Pendjari Biosphere Reserve in Benin. There were 76 species identified that had a high index value to people. The 10 most valued species were Parkia biglobosa, Adansonia digitata, Vitellaria paradoxa, Tamarindus indica, Lannea microcarpa, Vitex doniana, Hibiscus asper, Melochia corchorifolia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
3
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 31 publications
5
83
3
14
Order By: Relevance
“…Local people who consumed them fresh or dried or use them to produce fresh juice/brewed drinks (Marquet and Jansen, 2005) appreciates its fruits. L. microcarpa is ranked as the third IFT consumed by Ségou people in Mali (Diop, 2005) and the sixth most valued species around the Pendjari Reserve in Benin (Vodouhê et al, 2009). Assessment of the physicochemical properties of biodiesel from L. microcarpa seeds in Nigeria (Yunus et al, 2013) showed that most of the important properties were within the recommended standards for a biofuel grade biodiesel and suggested the potential of the seeds as a source of biodiesel.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Local people who consumed them fresh or dried or use them to produce fresh juice/brewed drinks (Marquet and Jansen, 2005) appreciates its fruits. L. microcarpa is ranked as the third IFT consumed by Ségou people in Mali (Diop, 2005) and the sixth most valued species around the Pendjari Reserve in Benin (Vodouhê et al, 2009). Assessment of the physicochemical properties of biodiesel from L. microcarpa seeds in Nigeria (Yunus et al, 2013) showed that most of the important properties were within the recommended standards for a biofuel grade biodiesel and suggested the potential of the seeds as a source of biodiesel.…”
Section: Introductionmentioning
confidence: 98%
“…Indigenous fruit trees (IFT) from natural habitats are sources of a number of non-timber forest products (NTFPs) that supply population needs in terms of food (edible fruits, leaves, roots and stems), energy (provision in fire woods and charcoal), cash income (from sales of plant organs and fruits), medicine (multiple recipes for disease treatment), etc. (Vodouhê et al, 2009;Poopola and Obembé, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling station located in the Pendjari River (Benin, West Africa). could likely impact the livelihood of local people and their involvement in PBR conservation activities (Vodouhê et al, 2009). Therefore, the investigation of oyster population dynamics was required to ascertain the current status of the bivalve and set sustainable management strategies for both population livelihood and wild fauna conservation.…”
Section: Figurementioning
confidence: 99%
“…Moreover, in the case of the Pendjari River, oyster exploitation partly took place inside the Pendjari Biosphere Reserve (PBR), one of the most important protected areas in Northern Benin. Owing to an ongoing participative approach, local dwellers were granted permission to harvest oyster within the protected area for food and sale in return for their contribution to wild fauna and Pendjari Biosphere Reserve protection (Vodouhê et al, 2009;Kiansi, 2011). Consequently, a collapse of oyster stocks 06p2…”
Section: Introductionmentioning
confidence: 99%